Short inertial sensor-based gait tests reflect perceived state fatigue in multiple sclerosis - Ibrahim, Alzhraa; Flachenecker, Felix; Gaßner, Heiko; Rothammer, Veit; Klucken, Jochen; Eskofier, Björn; Kluge, Felix (Multiple Sclerosis and Related Disorders, 2022)
Background: Multiple sclerosis (MS) is a chronic autoimmune inflammatory disease of the central nervous system, affecting more than 2.3 million people worldwide. Fatigue is among the most common symptoms in MS, resulting in reduced mobility and quality of life. The six-minute walking test (6MWT) is commonly used as a measure of fatigability for the assessment of state fatigue throughout treatment or rehabilitation programs. This ‘gold standard’ test is time-consuming and can be difficult and exhausting for some patients with high levels of disability or high rates of fatigue. Research question: Can short inertial sensor-based gait tests assess perceived state fatigue in MS patients? Methods: Sixty-five MS patients equipped with one sensor on each foot performed the 6 min walk test (6MWT) and the 25-foot walk (25FW, at both preferred and fastest speed). Perceived state fatigue was measured after each minute of the 6MWT, using the Borg rating. The highest of these ratings served as a measure of overall perceived state fatigue. Stride-wise spatio-temporal gait parameters were extracted from the 25FW and from the first minute, first 2 min, and first 4 min of the 6MWT. Principal component analysis was performed. Perceived state fatigue was predicted in a regression analysis, using the principal components of gait parameters as predictors. Statistical tests evaluated differences in performance between the full 6MWT, the shortened 6MWT, and the 25FW. Results: A mean absolute error of less than 2 points on the Borg rating was obtained using the shortened 6MWT and the 25FW. There were no significant differences between the prediction accuracy of the full 6MWT and that of the shortened gait tests. Significance: It is possible to use shortened gait tests when evaluating perceived state fatigue in MS patients using inertial sensors. Substituting them for long gait tests may reduce the burden of the testing on both patients and clinicians. Further, the approach taken here may prompt future work to explore the use of short bouts of real-world walking with unobtrusive inertial sensors for state fatigue assessment.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Accelerometer; Fatigue; IMU; MS; Short gait test